Compared to dematerialized money, cash increases impatience in intertemporal choice - Duclos, Rod (2019)
When it comes to trading time for money (or vice versa), people tend to be impatient and myopic. Often dramatically so. For illustration, half of people would rather collect $15 now than $30 in three months. This willingness to forego 50% of the reward to skip a 3‐month wait corresponds to an annual discount rate of 277%. This article investigates how money's physical form biases intertemporal choice. We ask, what happens to (im)patience (i.e., discount rates) when time is traded against cash rather than against an equivalent sum of dematerialized money? We find that intertemporal decisions pitting time against cash (rather than against dematerialized money) increase impatience. The underlying mechanism relates to the pain of parting from money. Letting go of cash (dematerialized money) we can have now is psychologically more (less) painful, which in turn reduces (increases) our willingness to wait for larger‐later payoffs. Importantly, heightening prevention focus (i.e., concerns for safety and security) moderates this bias. The article concludes by discussing the implications of the research, particularly for the psychology of saving behavior.